1988
DOI: 10.3109/00016358809004769
|View full text |Cite
|
Sign up to set email alerts
|

A clinical comparison of alternative alloys

Abstract: For the purpose of evaluating the clinical performance of 2 alternative dental casting alloys, 17 crowns made from the low-gold alloy Midas and 14 crowns made from the silver-palladium alloy Albacast were inserted at random into 23 patients. In each patient a high-gold type-3 alloy, JS C, served as a reference alloy. The patients were examined after 1 year with regard to tarnishing and certain factors such as plaque index, gingival index, and margin index. In addition, the California Dental Association's quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The principal observation in these studies was that somewhat more tarnish was seen for alloys with a reduced content of gold or without gold altogether. Also, more roughness was seen on the surfaces of some of the alternative alloys (2,3). Sturdevant et al (4), who evaluated 15 low-gold casting alloys after 8 years, noted some loss of polish and tarnish, although the authors concluded that these surface changes were well within the ranges for clinical acceptability.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The principal observation in these studies was that somewhat more tarnish was seen for alloys with a reduced content of gold or without gold altogether. Also, more roughness was seen on the surfaces of some of the alternative alloys (2,3). Sturdevant et al (4), who evaluated 15 low-gold casting alloys after 8 years, noted some loss of polish and tarnish, although the authors concluded that these surface changes were well within the ranges for clinical acceptability.…”
mentioning
confidence: 92%
“…Thus, only short-term clinical data on the correlation between gingival inflammation and alternative alloys exist. Therefore, the aim of the present study was to follow up the results of the previous 1-year report (3) with special attention to tarnish, roughness formation, and changes in the oral mucosa adjacent to the restorations made from alternative dental casting alloys.…”
mentioning
confidence: 99%